THE EFFECT OF ORGANIZATIONAL ACTIVITY, SELF EFFICCY AND SOFT SKILLS ON WORK READINESS OF FEB STUDENTS AT YPPI UNIVERSITY REMBANG - Adelia Ika Damayanti; Ayunda Riska Rofiatus Sa'adah (SOSIOEDUKASI, 2025)
This study aims to prove the influence of organizational activity, self efficacy, and soft skills towards readiness work FEB students of YPPI University Rembang. Population in the study this is student Faculty of Economics and Business, YPPI University, Rembang. Sample from study This is 112 students Faculty of Economics and Business, YPPI University, Rembang. Selection techniques sample using purposive sampling. Data analysis techniques using analysis multiple linear regression. Research results This show that activity organize influential positive significant to readiness work, self efficacy influential positive no significant to readiness work and soft skills influential positive significant to readiness work. Based on results research, can concluded that activity organizational and soft skills are influential positive and significant to readiness work students, while self efficacy influential positive however no significant to readiness work. This is show that the more tall level activity organizational and soft skills possessed students, then the more high level​ readiness work student.